Greece : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report, 1997)
This Selected Issues paper and Statistical Appendix reviews fiscal developments in Greece, comparing its revenue and expenditure patterns with a number of comparator country averages, and discusses prospects. The paper focuses on the evolution and tax-determinants of the most widely followed indicator of the health and competitiveness of a banking system, the lending-deposit spread. It also brings to bear a wide variety of indicators and econometric techniques to the problem of understanding the state and prospects of the banking system.